Innovations in the Malaysian furniture industry - Subramaniam, Hasshviny (2018)
The furniture sector in Malaysia has commendably thrived and has significantly contributed to the economy wealth of this country. However, over the years the state of the furniture industry has been on decline, requiring the Malaysian Furniture industry to innovate in order to survive the global market. Therefore, to achieve this goal this study seeks to explore the level of innovativeness in the Malaysian Furniture industry. This study used quantitative research approach where the primary data was collected via interviews and was analyzed using SPSS software. The main findings of this study revealed that, currently low innovation activities are taking place in the Malaysian Furniture Industry despites its successful milestones over the decades. There are mainly three types of innovations adapted in the firm such as product innovation followed by process innovation and market innovation. These innovations were found to be in accordance with its main objective which was to improve the product quality. The analysis on motivation showed that, the firms are mainly motivated to carry out innovation activities by internal and external resources. R&D department and customers were among the top internal and external factors that contributed to the sources of innovation. These factors were found to play significant roles in contributing to a firm’s success.